Issues of Complex Mahallas Development - D.A. Nazarova; G.X. Ziyadullayev (Genius Journals, 2023)
The historical mahallas of our country have real exoticism, a sense of authenticity, charming corners with national flavor. In order to preserve these territories, a number of decrees and resolutions have been developed in our country
Keywords: Mahalla; history; tourism; cultural heritage